2022
DOI: 10.3390/ijerph191710903
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Duration of Traffic Incidents by Hybrid Deep Learning Based on Multi-Source Incomplete Data

Abstract: Traffic accidents causing nonrecurrent congestion and road traffic injuries seriously affect public safety. It is helpful for traffic operation and management to predict the duration of traffic incidents. Most of the previous studies have been in a certain area with a single data source. This paper proposes a hybrid deep learning model based on multi-source incomplete data to predict the duration of countrywide traffic incidents in the U.S. The text data from the natural language description in the model were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Therefore the BiGRU-CNN has the highest F1 value of 0.527. This finding is consistent with Shang et al [ 33 ] who have reported the importance of deep learning algorithms in the duration prediction of traffic accidents by text data. In addition, this study confirms that the newly established structured features extracted from text data by the one-hot model substantially enhance the prediction effects of deep learning algorithms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore the BiGRU-CNN has the highest F1 value of 0.527. This finding is consistent with Shang et al [ 33 ] who have reported the importance of deep learning algorithms in the duration prediction of traffic accidents by text data. In addition, this study confirms that the newly established structured features extracted from text data by the one-hot model substantially enhance the prediction effects of deep learning algorithms.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Ji et al predicted the duration of highway accidents based on the text data associated with 969 traffic accident records and social network information, and an average mean absolute percentage error (MAPE) of less than 22% was obtained for accident durations within the range of 0–180 min [ 32 ]. Shang et al established a mixed deep learning model combining latent Dirichlet allocation-BiLSTM (LDA-BiLSTM) networks to predict the duration of traffic accidents based on an analysis of the text data associated with 78,317 traffic incidents [ 33 ]. However, the traffic accident durations considered in this work were limited to within 90 min, and far too little attention was given toward capturing multi-mode data via the fusion of structured data and text data.…”
Section: Introductionmentioning
confidence: 99%
“…Some models combine the strengths of statistical models and machine learning models. Hybrid models [3,27,30] can be more accurate than either statistical models or machine learning models alone. One example of a hybrid model is the Bayesian network [31].…”
Section: Machine Learning Approachmentioning
confidence: 99%
“…The term "duration" in the context of a traffic incident refers to the overall time period starting from when the incident takes place until the arrival of traffic police at the scene and the completion of handling. Generally, the duration of a traffic incident can be divided into the following stages [3], as illustrated in Figure 1 below.…”
Section: Introductionmentioning
confidence: 99%